2010
DOI: 10.1007/s10995-010-0595-6
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Depression and Birth Outcomes in a Healthy Start Project

Abstract: Given the risk of adverse perinatal outcomes associated with a depressive disorder, the Health Resources and Services Administration’s (HRSA) Maternal and Child Health Bureau (MCHB) from 2001–2005 devoted resources through the Federal Healthy Start Initiative to screen pregnant women for depression and link them with services. In this report, we present the evaluation of a program that screened for depression and provided services for women with depressive symptoms or psychiatric distress in pregnancy to asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
86
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(105 citation statements)
references
References 22 publications
(14 reference statements)
2
86
0
4
Order By: Relevance
“…In four of them there was no statistical significance of the effect of DAS on PTB, as CI contained the null value. Overall, eight studies reported a significantly increased risk for PTB 8,[12][13][14][15][16][17][18] ; one study reported a positive predictive value between exposure and outcome, 19 and five studies reported no statistically significant increase in risk. 11,[20][21][22][23] Both independent and mediated (through antidepressant use) effects for depression were identified across studies.…”
Section: Depressionmentioning
confidence: 99%
“…In four of them there was no statistical significance of the effect of DAS on PTB, as CI contained the null value. Overall, eight studies reported a significantly increased risk for PTB 8,[12][13][14][15][16][17][18] ; one study reported a positive predictive value between exposure and outcome, 19 and five studies reported no statistically significant increase in risk. 11,[20][21][22][23] Both independent and mediated (through antidepressant use) effects for depression were identified across studies.…”
Section: Depressionmentioning
confidence: 99%
“…childbirth outcomes, such as preterm delivery and low birth weight, 26,27 and to detrimental effects on maternal sensitivity in the postpartum period. 28,29 Specifically, mothers who are more sensitive and responsive to their children are more likely to have children with secure attachment.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Depression and anxiety have been linked to somatic complaints, gestational and obstetric complications, stillbirth, premature birth, low birth weight, low Apgar scores, smaller head circumference, alterations in fetal motor activity, affected fetal heart rate patterns and major congenital anomalies. [3][4][5][6][7][8] Some studies found the prevalence of similar antenatal anxiety across all three trimesters, but many Previous studies reported that antenatal anxiety varied at different trimesters of pregnancy and high anxiety was found during first and third trimester.…”
Section: Introductionmentioning
confidence: 99%